Impact of molybdenum out diffusion and interface quality on the performance of sputter grown CZTS based solar cells - Dalapati, Goutam Kumar (2017)
We have investigated the impact of Cu2ZnSnS4-Molybdenum (Mo) interface quality on the performance of sputter-grown Cu2ZnSnS4 (CZTS) solar cell. Thin film CZTS was deposited by sputter deposition technique using stoichiometry quaternary CZTS target. Formation of molybdenum sulphide (MoSx) interfacial layer is observed in sputter grown CZTS films after sulphurization. Thickness of MoSx layer is found ~142 nm when CZTS layer (550 nm thick) is sulphurized at 600 °C. Thickness of MoSx layer significantly increased to ~240 nm in case of thicker CZTS layer (650 nm) under similar sulphurization condition. We also observe that high temperature (600 °C) annealing suppress the elemental impurities (Cu, Zn, Sn) at interfacial layer. The amount of out-diffused Mo significantly varies with the change in sulphurization temperature. The out-diffused Mo into CZTS layer and reconstructed interfacial layer remarkably decreases series resistance and increases shunt resistance of the solar cell. The overall efficiency of the solar cell is improved by nearly five times when 600 °C sulphurized CZTS layer is applied in place of 500 °C sulphurized layer. Molybdenum and sulphur diffusion reconstruct the interface layer during heat treatment and play the major role in charge carrier dynamics of a photovoltaic device.